Direct assessment of renal mitochondrial redox state using hyperpolarized 13C‐acetoacetate. Issue 4 (3rd January 2018) - von Morze, Cornelius; Ohliger, Michael A.; Marco‐Rius, Irene; Wilson, David M.; Flavell, Robert R.; Pearce, David; Vigneron, Daniel B.; Kurhanewicz, John; Wang, Zhen J.
Abstract : Purpose: The purpose of this study was to investigate the hyperpolarized ketone body 13 C‐acetoacetate (AcAc) and its conversion to 13 C‐β‐hydroxybutyrate (βOHB) in vivo, catalyzed by β‐hydroxybutyrate dehydrogenase (BDH), as a novel direct marker of mitochondrial redox state. Methods: [1, 3‐ 13 C2 ]AcAc was synthesized by hydrolysis of the ethyl ester, and hyperpolarized via dissolution DNP. Cold storage under basic conditions resulted in sufficient chemical stability for use in hyperpolarized (HP) MRI studies. Polarizations and relaxation times of HP [1, 3‐ 13 C2 ]AcAc were measured in a clinical 3T MRI scanner, and 8 rats were scanned by dynamic HP 13 C MR spectroscopy of a slab through the kidneys. Four rats were scanned after acute treatment with high dose metformin (125 mg/kg, intravenous), which is known to modulate mitochondrial redox via inhibition of mitochondrial complex I. An additional metformin‐treated rat was scanned by abdominal 2D CSI (8 mm × 8 mm). Results: Polarizations of 7 ± 1% and 7 ± 3%, and T1 relaxation times of 58 ± 5 s and 52 ± 3 s, were attained at the C1 and C3 positions, respectively. Rapid conversion of HP AcAc to βOHB was detected in rat kidney in vivo, via the C1 label. The product HP βOHB was resolved from closely resonating acetate. Conversion to βOHB was also detected via 2D CSI, in both kidney as well as liver regions. Metformin treatment resulted in a significant increase (40%, P = 0.01) of conversion of HP AcAc to βOHB. Conclusion: Rapid conversion of HP AcAc to βOHB was observed in rat kidney in vivo and is a promising new non‐invasive marker of mitochondrial redox state. Magn Reson Med 79:1862–1869, 2018. © 2017 International Society for Magnetic Resonance in Medicine.